2006
DOI: 10.1130/b25956.1
|View full text |Cite
|
Sign up to set email alerts
|

Small-volume basaltic volcanoes: Eruptive products and processes, and posteruptive geomorphic evolution in Crater Flat (Pleistocene), southern Nevada

Abstract: Five Pleistocene basaltic volcanoes in Crater Flat (southern Nevada) demonstrate thc complexity of eruption processes associated with small-volume basalts and the cffccts of initial emplacement characteristics on post-eruptive geomorphic evolution of thc volcanic surfaces. The volcanoes record eruptive processes in their pyroclastic facies ranging from "classical" Strombolian mechanisms to, potentially, violent Strombolian mechanisms. Cone growth was accompanied, and sometimes disrupted, by effusion of lavas f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
48
0
4

Year Published

2007
2007
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(54 citation statements)
references
References 39 publications
2
48
0
4
Order By: Relevance
“…During their short-lived eruption usually small magma volumes are involved producing small-scale volcanic landforms [38,40]. In spite of this simple model, current research showed numerous evidences that volcanoes considered earlier as monogenetic, including maar-diatremes, can be complex both from a volcanic edifice and chemical point of view [103,109]. This paradox can be solved through the introduction of an intermediary type in volcano classification where complex monogenetic volcanoes are somehow distinguished from sensu stricto monogenetic and purely polygenetic volcanic landforms [109].…”
Section: Maar/diatreme Volcanoesmentioning
confidence: 99%
See 3 more Smart Citations
“…During their short-lived eruption usually small magma volumes are involved producing small-scale volcanic landforms [38,40]. In spite of this simple model, current research showed numerous evidences that volcanoes considered earlier as monogenetic, including maar-diatremes, can be complex both from a volcanic edifice and chemical point of view [103,109]. This paradox can be solved through the introduction of an intermediary type in volcano classification where complex monogenetic volcanoes are somehow distinguished from sensu stricto monogenetic and purely polygenetic volcanic landforms [109].…”
Section: Maar/diatreme Volcanoesmentioning
confidence: 99%
“…In spite of this simple model, current research showed numerous evidences that volcanoes considered earlier as monogenetic, including maar-diatremes, can be complex both from a volcanic edifice and chemical point of view [103,109]. This paradox can be solved through the introduction of an intermediary type in volcano classification where complex monogenetic volcanoes are somehow distinguished from sensu stricto monogenetic and purely polygenetic volcanic landforms [109]. This problem is critical while interpreting large maar-diatreme volcanoes that evidently represent complex volcanic features which cannot be explained to have been formed in a single eruptive episode [109].…”
Section: Maar/diatreme Volcanoesmentioning
confidence: 99%
See 2 more Smart Citations
“…During the period from about 9 to 11 million years ago, this felsic volcanism transitioned to basaltic magmatism with four recognized pulses, including the 80,000-year-old Lathrop Wells event and several 1-million-year-old events in Crater Flat adjacent to Yucca Mountain. General agreement is that future igneous activity is likely to be a small-volume, single-episode basaltic event similar to the Lathrop Wells volcano [Valentine et al, 2006] with comparable power, duration, type of erupted products, spatial relationship to the topographic surface, geochemical characteristics of the magma, and feeder igneous dike characteristics.…”
Section: What Is the Nature Of Possible Igneous Activity?mentioning
confidence: 53%